Effect of integrated reporting on company performance: evidence from selected banking institutions listed on the Zimbabwe stock exchange - Makasi, Barbra (Midlands State University, 2018)
The purpose of this study was to assess the effect of Integrated Reporting on company performance in the banking sector in Zimbabwe with CBZ, ZB and NMB as the cases of study. While Integrated reporting is the way of reporting being adopted by many companies since its inception by the Integrated Reporting Council in 2011, the link between the its adoption and the improvement of the performance of banks that adopted it still remains a grey area. Indeed many studies have predominantly focused on the level of adoption and the quality of reports, with the majority emanating from developed countries creating a dearth gap in the literature that address the effect of Integrated Reporting on company performance. A survey research design was used in line with the objectives of the study which is largely quantitative. A structured questionnaire was used. The questionnaire was structured in such a way that it captured all the five hypotheses formulated. The five hypotheses were organized in sections which constituted parts of the questionnaire. The draft questionnaire was pilot tested to a group of 10 randomly selected CBZ, NMB and ZB staff personnel at various branches. The sample size was statistically determined based on the current population size of 1800 employees for the three banks. After cleaning the data, the analysis of data proceeded through the use of IBM SPSS. The extraction method used was Categorical Principal Component Analysis (CATPCA). Results extracted confirmed all the five hypotheses at 5% level of significance. Evidence provided confirmed that Integrated Reporting is critical in enhancing company performance. While this research provided exciting ground-breaking discoveries, many limitations existed. This included methodological and sample size limitations. Therefore further research can be conducted using a bigger sample size or conduct a similar study from a qualitative research perspective. Such a wider geographical delimitation may help understand the relationship between Integrated Reporting and the performance of banking institutions.